Disharmoni Kewenangan Antara Pusat dan Daerah dalam Penanganan Bencana Ekologis di Aceh : Kajian Hukum Administrasi Negara atas Implementasi Otonomi Daerah - Muhammad Alfarisi; Nabillah Riniaini Panjaitan; Fani Fani (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2026)
Environmental disasters in regions with special autonomy present complex jurisdictional challenges, as demonstrated by the flash floods that struck Aceh Province between November and December 2025. The disaster caused casualties, extensive infrastructure damage, and revealed jurisdictional tensions between the central government and the Aceh Government in coordinating disaster response. This study examines the regulation of disaster management authority from the perspective of Administrative Law, identifies patterns of jurisdictional discord during the 2025 Aceh flood response, and proposes an ideal model for restructuring authority within the special autonomy framework. Using normative legal research with a prescriptive-analytical approach, the study applies statutory, conceptual, and case-based methods to analyze primary and secondary legal materials qualitatively. The findings show that national disaster management regulations and Aceh’s special autonomy framework operate in parallel without adequate normative integration, creating structural jurisdictional gaps. These gaps are reflected in four major forms of discord: ambiguity in emergency status declaration, fragmented command structures, disputes over funding allocation, and overlapping authority in ecosystem management. The study concludes that these conflicts are systemic rather than incidental. It proposes the concept of asymmetric disaster authority as a contribution to Administrative Law and recommends harmonizing regulations through special coordination mechanisms, amendments to disaster-related qanuns, and the institutionalization of joint command protocols to strengthen disaster governance in special autonomy regions.